2005
DOI: 10.1111/j.1398-9995.2005.00717.x
|View full text |Cite
|
Sign up to set email alerts
|

Rhinitis is an independent risk factor for developing cough apart from colds among adults

Abstract: Rhinitis is a significant and independent risk factor for developing cough among adults. Further research is needed to assess potential implications in terms of prevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
51
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 26 publications
(35 reference statements)
0
51
0
1
Order By: Relevance
“…The proportion of those with airflow obstruction in the absence of any respiratory diagnosis is 10.96% in the whole population sample (13.77% in males; 8.24% in females). In the Pisa sample, rhinitis has been shown to be an independent risk factor for developing cough, with the exception of common colds, in a 6-yr follow-up, without any difference between males and females [41].…”
Section: Changing Copd Epidemiologymentioning
confidence: 87%
See 1 more Smart Citation
“…The proportion of those with airflow obstruction in the absence of any respiratory diagnosis is 10.96% in the whole population sample (13.77% in males; 8.24% in females). In the Pisa sample, rhinitis has been shown to be an independent risk factor for developing cough, with the exception of common colds, in a 6-yr follow-up, without any difference between males and females [41].…”
Section: Changing Copd Epidemiologymentioning
confidence: 87%
“…Finally, some original findings on gender-related differences from the Po Delta [7,[36][37][38][39][40] and Pisa [38,39,41] surveys in Italy are presented in this section.…”
Section: Copd and Females Summarymentioning
confidence: 99%
“…It can be caused by a number of factors (1161,(2144)(2145)(2146), including postinfectious cough (2147), allergic rhinitis (2148)(2149)(2150), infection, rhinosinusitis (2151), asthma, COPD, gastro-esophageal reflux (2152), environmental stimuli such as tobacco smoke or occupational exposure (563,564), bronchiectasis (2153), interstitial lung disease, congestive heart failure, drugs (ACE inhibitors, ß-blockers) (2154), thyroid disorders and psychogenic cough.…”
Section: Chronic Coughmentioning
confidence: 99%
“…Rhinitis is an independent risk factor for both recurrent cough and wheezing during childhood and adulthood (2148)(2149)(2150). In patients with seasonal rhinitis, dry cough is common and often the predominant non-nasal symptom (1940).…”
Section: Chronic Coughmentioning
confidence: 99%
“…Allergic rhinitis is often associated with asthma and a global perspective is needed (46,47). In some studies, it has been found that NAR is also associated with asthma (7,14,48). However, the importance of the association between the two sites of the airways needs to be better assessed comparing allergic and nonallergic patients, particularly in patients with uncontrolled asthma (49,50).…”
Section: Epidemiologic Studiesmentioning
confidence: 99%